Farmers’ free time: an opportunity to increase income - Man, Norsida; Ismaila, Sadiya Sami (Universiti Putra Malaysia Press, 2015)
This book presents the agricultural development in Malaysia, issues and challenges in paddy farming and revealed the importance and the role of off-farm employment in increasing farmers’ income in granary area. It also covers and explains the situation of paddy farming in two granary areas which are Muda Area in Kedah and Kemasin Semerak Area in Kelantan. The Muda Area is the biggest area with high productivity in paddy while Kemasin Semerak are among the area that produce low in productivity. Paddy farming is very importance and play a vital role in food security and agriculture development in Malaysia. Beside the high cost in paddy production, government of Malaysia need to determine and convince farming community to produce our principal food rice for Malaysian sustainably and give them high income and profit.